EULAR recommendations for cardiovascular risk management in rheumatic and musculoskeletal diseases, including systemic lupus erythematosus and antiphospholipid syndrome. Issue 6 (2nd February 2022) - Drosos, George C; Vedder, Daisy; Houben, Eline; Boekel, Laura; Atzeni, Fabiola; Badreh, Sara; Boumpas, Dimitrios T; Brodin, Nina; Bruce, Ian N; González-Gay, Miguel Ángel; Jacobsen, Søren; Kerekes, György; et al.
Abstract : Objective: To develop recommendations for cardiovascular risk (CVR) management in gout, vasculitis, systemic sclerosis (SSc), myositis, mixed connective tissue disease (MCTD), Sjögren's syndrome (SS), systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). Methods: Following European League against Rheumatism (EULAR) standardised procedures, a multidisciplinary task force formulated recommendations for CVR prediction and management based on systematic literature reviews and expert opinion. Results: Four overarching principles emphasising the need of regular screening and management of modifiable CVR factors and patient education were endorsed. Nineteen recommendations (eleven for gout, vasculitis, SSc, MCTD, myositis, SS; eight for SLE, APS) were developed covering three topics: (1) CVR prediction tools; (2) interventions on traditional CVR factors and (3) interventions on disease-related CVR factors. Several statements relied on expert opinion because high-quality evidence was lacking. Use of generic CVR prediction tools is recommended due to lack of validated rheumatic diseases-specific tools. Diuretics should be avoided in gout and beta-blockers in SSc, and a blood pressure target <130/80 mm Hg should be considered in SLE. Lipid management should follow general population guidelines, and antiplatelet use in SLE, APS and large-vessel vasculitis should follow prior EULAR recommendations. A serum uric acid level <0.36 mmol/L (<6 mg/dL) in gout, and disease activity control and glucocorticoid dose minimisation in SLE and vasculitis, are recommended. Hydroxychloroquine is recommended in SLE because it may also reduce CVR, while no particular immunosuppressive treatment in SLE or urate-lowering therapy in gout has been associated with CVR lowering. Conclusion: These recommendations can guide clinical practice and future research for improving CVR management in rheumatic and musculoskeletal diseases.